Reciprocity and the recognition and enforcement of foreign judgments: a lot of bark but not much bite - Elbalti, Béligh (Journal of private international law, 2017)
This article's main purpose is to analyse the implications of some recent developments relating to reciprocity on the practice of the recognition and enforcement of foreign judgments. It shows that reciprocity has become a toothless principle that should not pose serious concern. It also argues that even if it is not abolished entirely, reciprocity no longer plays a significant role in the field of the recognition and enforcement of foreign judgments, and therefore, should not be an issue of concern for jurisdictions that accept the principle of recognition. This is because, the test for establishing reciprocity has now become so relaxed that the requirement will normally be met if it is shown that the courts of the rendering State are likely to recognize the enforcing State's judgments. In other words, reciprocity can prove to be a serious hurdle only when it comes to the recognition of judgments rendered in a State that manifestly adheres to an unduly restrictive recognition regime such as regimes where recognition and enforcement are subject to the existence of a treaty or based on the outdated practice of révision au fond.